2017
DOI: 10.1016/j.jvs.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of In Situ Fenestration of Aortic Endografts

Abstract: Objective/Background: The management of aortic graft infection (AGI) is highly complex and in the absence of a universally accepted case definition and evidence-based guidelines, clinical approaches and outcomes vary widely. The objective was to define precise criteria for diagnosing AGI.Methods: A process of expert review and consensus, involving formal collaboration between vascular surgeons, infection specialists, and radiologists from several English National Health Service hospital Trusts with large vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…The cTAG is covered with expanded polytetrafluoroethylene (ePTFE), which has proved easier to puncture than other endograft fabrics in in vitro experiments. 11 Therefore, this can facilitate the needle penetration and shorten the cerebral ischaemic time in LCCA and BCT revascularisation. In addition, it has also been reported that the orifices created on ePTFE membrane by plain balloons are markedly circular not elliptical, 12 which can better conform to the bridging endografts and diminish the chance of endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…The cTAG is covered with expanded polytetrafluoroethylene (ePTFE), which has proved easier to puncture than other endograft fabrics in in vitro experiments. 11 Therefore, this can facilitate the needle penetration and shorten the cerebral ischaemic time in LCCA and BCT revascularisation. In addition, it has also been reported that the orifices created on ePTFE membrane by plain balloons are markedly circular not elliptical, 12 which can better conform to the bridging endografts and diminish the chance of endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…In situ fenestration of standard stent grafts is another option to extend the proximal landing zone by covering the supra-aortic branches and performing a fenestration via a retrograde access in vivo. 217,218 Graft perforations can be performed by laser or mechanical means. This technique is new, and long-term data in humans are missing.…”
Section: Classmentioning
confidence: 99%
“…Fenestrated stent-grafting in the aortic arch is technically challenging due to difficulties in stent-graft orientation and fenestration positioning. In situ fenestration techniques might avoid these problems, but because of possible issues with stent-grafts durability and ischemic complications during temporary carotid arteries coverage, this technique has not been widely adopted [16,17,18]. In recent years, arch branched endografts have been developed as a new technique for revascularization of supra-aortic branches.…”
Section: Discussionmentioning
confidence: 99%